2016
DOI: 10.1155/2016/9041636
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Analysis ofStaphylococcus aureusClinical Isolates from Hospitalized Patients

Abstract: Staphylococcus aureus is opportunistic human as well as animal pathogen that causes a variety of diseases. A total of 100 Staphylococcus aureus isolates were obtained from clinical samples derived from hospitalized patients. The presumptive Staphylococcus aureus clinical isolates were identified phenotypically by different biochemical tests. Molecular identification was done by PCR using species specific 16S rRNA primer pairs and finally 100 isolates were found to be positive as Staphylococcus aureus. Screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 32 publications
0
43
2
Order By: Relevance
“…The results of current study are disagreed with studies done by Karmakar et al [9] and Boucher and Corey [12], in which they separately reported that the frequency of MRSA infections increases continuously in hospital-associated infection.…”
Section: Detection Of 16srrna Meca and Pvl Genes By Polymerase Chaincontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of current study are disagreed with studies done by Karmakar et al [9] and Boucher and Corey [12], in which they separately reported that the frequency of MRSA infections increases continuously in hospital-associated infection.…”
Section: Detection Of 16srrna Meca and Pvl Genes By Polymerase Chaincontrasting
confidence: 99%
“…Karmakar et al [9] mentioned that among 165 samples, 100 strains (60.60%) were isolated from a selective MSA media and then these isolates were identified as S. aureus by different biochemical tests. Gram staining, catalase, coagulase, and thermonuclease were important phenotypic identifying markers of S. aureus.…”
Section: Detection Of 16srrna Meca and Pvl Genes By Polymerase Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Units of β-Lactamase: One unit of β-lactamase is defined as the amount of enzyme that hydrolyzes benzyl penicillin at the rate of 1 µmole/min (Sykes & Nordstrom, 1972;Karmakar, Dua & Ghosh, 2016).…”
Section: Quantification Of the Lactamase Activitymentioning
confidence: 99%
“…Thus in the last decades, staphylococci and their toxins had also emerged as important and potential pathogen for human and animal [3,5]. The success of S. aureus as a pathogen and its ability to cause such a wide range of infections are the result of its extensive virulence factors such as extracellular enzymes and biofilm formation beside toxins [6,7]. lipases produced from S. aureus could increase the rate of food deterioration through their action on lipids causing accumulation of intermediate and end products that change the flavor of foods [8,9].…”
mentioning
confidence: 99%